Environmental Economics: Addressing Global Environmental Challenges through Policy (Global Journal of Human-Social Science, 2024)
Environmental issues have become increasingly complex and interconnected posing significant challenges on a global scale The international community has recognized the urgency of addressing these challenges leading tothe development of various environmental laws and initiatives at both the international and national levels Efforts have focused on key areas such as the relationship between environmental protection and economic development transboundary pollution global environmental phenomena and industrial emergencies While gaps remain in legally binding agreements governments and non-governmental organizations have collaborated to promote environmental awareness strengthen international cooperation and develop scientific means of environmental protection To effectively address these environmental challenges a comprehensive and coordinated approach is necessary involving governments businesses civil society and the general public working in tandem to strike a delicate balance between economic progress and environmental sustainability Moreover this research paper examines the various national level initiatives undertaken to address pressing global environmental issues
Keywords: environmental/ecological economics; sustainable economics; climate change; environmental policy; international environmental law